New species of Chimerothalassius Shamshev & Grootaert (Diptera: Dolichopodidae: Parathalassiinae) from the West Indies and Costa Rica - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2018)
Chimerothalassius runyoni sp. nov. is described from rocky coastlines of Montserrat and Dominica, and the genus is newly recorded from the Pacific coast of Costa Rica, based on female specimens of an undescribed species.